2016
DOI: 10.1021/acs.bioconjchem.6b00405
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Paclitaxel-Loaded Gold Nanoparticles for Tumor-Targeted Drug Delivery

Abstract: The synthesis of a series of thiolated paclitaxel analogs is described as part of a novel nanomedicine program aimed at developing formulations of paclitaxel that will bind to gold nanoparticles for tumor targeted drug delivery. Preliminary evaluation of the new nanomedicine comprised of 27 nm gold nanoparticles, tumor necrosis factor alpha (TNFα), thiolated polyethylene glycol (PEG-Thiol) and one of several thiolated paclitaxel analogs is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…Devi et al have studied and characterized PTX‐polymeric nanoparticles by Fourier transform infrared (FT‐IR) and Raman spectroscopies . These spectroscopic analysis showed that the specific functional groups of the PTX‐polymeric nanoparticle have the same chemical characteristics than the pure paclitaxel drug, indicating that the molecular interaction with the NP surface does not affect the chemical structure of the drug . Contrary to this study, even if we have involved similar ingredients (drug, polymer) chelated to gold ions in order to form gold nanoparticles, the spectroscopical fingerprints of our final nanodrug are not peculiar compared to the free drugs.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Devi et al have studied and characterized PTX‐polymeric nanoparticles by Fourier transform infrared (FT‐IR) and Raman spectroscopies . These spectroscopic analysis showed that the specific functional groups of the PTX‐polymeric nanoparticle have the same chemical characteristics than the pure paclitaxel drug, indicating that the molecular interaction with the NP surface does not affect the chemical structure of the drug . Contrary to this study, even if we have involved similar ingredients (drug, polymer) chelated to gold ions in order to form gold nanoparticles, the spectroscopical fingerprints of our final nanodrug are not peculiar compared to the free drugs.…”
Section: Resultsmentioning
confidence: 67%
“…DTX is more water soluble than PTX due to its chemical structure. [7b] In previous studies, DTX and PTX were derivatized at the hydroxyl group in the C‐2′ position to form a derivatized acid ester . The free hydroxyl group in this position is essential for anticancer activity .…”
Section: Resultsmentioning
confidence: 99%
“…[52]. The PTX-loaded redox-sensitive nanoparticles has shown greater in vitro cytotoxicity and apoptosis-inducing ability against CD44 over-expressed A549 tumor cells in comparison to the redox-insensitive nanoparticles [53]. In an in-vivo study, the PTX-loaded HSV nanoparticles exhibited an enhanced antitumor efficacy in a A549 mouse xenograft model [54].…”
Section: Lung Cancermentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In this regard, gold nanoparticles are widely used in many research fields, including bio-sensin, [9][10][11] photothermal cancer therapy, 12,13 catalysis, 14,15 and drug delivery mechanisms. 16,17 Recently, two-dimensional (2D) triangular gold nanoplates (AuNPs) have been gaining considerable interest due to their unique optical properties and extremely high anisotropy. [18][19][20] 2D anisotropic AuNPs have large surface areas, sharp corners, and edges which can greatly enhance any applied electric fields.…”
Section: Introductionmentioning
confidence: 99%